Melanoma risk perception and prevention behavior among African-Americans: the minority melanoma paradox - Goldenberg A; Vujic I; Sanlorenzo M; Ortiz-Urda S (Dove Medical Press, 2015)
Alina Goldenberg,1 Igor Vujic,2,3 Martina Sanlorenzo,2,4 Susana Ortiz-Urda2 1Department of Internal Medicine/Dermatology, University of California, San Diego, 2Mt Zion Cancer Research Center, University of California San Francisco, San Francisco, CA, USA; 3Department of Dermatology, The Rudolfstiftung Hospital, Academic Teaching Hospital, Medical University Vienna, Vienna, Austria; 4Section of Dermatology, Department of Medical Sciences, University of Turin, Turin, Italy Introduction: Melanoma is the most deadly type of skin cancer with 75% of all skin cancer deaths within the US attributed to it. Risk factors for melanoma include ultraviolet exposure, genetic predisposition, and phenotypic characteristics (eg, fair skin and blond hair). Whites have a 27-fold higher incidence of melanoma than African-Americans (AA), but the 5-year survival is 17.8% lower for AA than Whites. It is reported continuously that AA have more advanced melanomas at diagnosis, and overall lower survival rates. This minority melanoma paradox is not well understood or studied. Objective: To explore further, the possible explanations for the difference in melanoma severity and survival in AA within the US. Methods: Qualitative review of the literature. Results: Lack of minority-targeted public education campaigns, low self-risk perception, low self-skin examinations, intrinsic virulence, vitamin D differences, and physician mistrust may play a role in the melanoma survival disparity among AA. Conclusion: Increases in public awareness of melanoma risk among AA through physician and media-guided education, higher index of suspicion among individuals and physicians, and policy changes can help to improve early detection and close the melanoma disparity gap in the future. Keywords: acral, advanced, African-American, disparity, melanoma, survival